Efficacy of laser photoacoustic streaming in paediatric root canal disinfection - An Ex-Vivo study - Chandrashekar Murugesh Yavagal; Viplavi Chavan Patil; Puja Chandrashekar Yavagal; N Kiran Kumar; Madhu Hariharan; Sachin B Mangalekar (Wolters Kluwer Medknow Publications, 2021)
Background: Various techniques have been employed to enhance the root canal disinfection rate using sodium hypochlorite (NaOCl) as an irrigant. Photon initiated photo-acoustic streaming using lasers is a newer method of endodontic disinfection. Aim: The aim of this study is to evaluate and compare the efficacy of photo-initiated photoacoustic streaming and conventional irrigation technique using 2.5% NaOCl for root canal disinfection in primary teeth. Setting and Design: Laboratory setting and ex-vivo design. Materials and Methods: Twenty extracted primary teeth were selected in which Enterococcus faecalis incubation was done in the root canals and bacterial counts were obtained before the intervention. The teeth were randomly allocated into two groups. Group I samples were irrigated with conventional syringe method using 2.5% NaOCl and Group II samples were irrigated using photon-initiated photo-acoustic streaming method with erbium-doped yttrium aluminum garnet laser (wavelength - 2940 nm). Postintervention samples were obtained, and bacterial colony count was done. Wilcoxon Signed- Ranks Test and Mann-Whitney test were applied to test the intragroup and intergroup differences in the bacterial counts. Results: Postintervention results showed no bacterial growth in the canals irrigated using Laser (P = 0.004) whereas, fewer bacterial colonies were observed in NaOCl group (P = 0.005). There was statistically significantly higher reduction in E. faecalis counts in Laser Activated irrigation (LAI) group compared to NaOCl group (P < 0.05). Conclusion: Total elimination of E. faecalis counts was obtained by the use of laser activated NaOCl irrigation in the infected root canals, hence, it can be considered as an effective method for pediatric endodontic disinfection.